Between Human Rights Protection and Criminal Procedure – Analysis of Approaches to Investigative Interviewing - Wawrzyńczak, Michał (Central European Academy Law Review, 2025)
Human rights, including the protection against torture or degrading and inhuman treatment, should be guiding law enforcement agencies’ actions. Research shows that a vital moment of either their violation or realization occurs during the interrogation as a procedural activity. This paper will discuss the relationship between the above-mentioned human rights and interrogation in a procedural setting, with particular emphasis on the pre-trial stage. The methodological basis of this paper includes dogmatic-legal, theoretical-legal and partially empirical methods. The central axis of consideration is the evolution of questioning techniques, starting from the analysis of coercive interrogation techniques – with the most popular Reid technique – to non-coercive methods, including the most recent proposal – the Méndez Principles. Besides that, the Author briefly considers model-level solutions on techniques permitted during the procedural activity of questioning. The analysis showed that, to date, the most popular method of interrogation – the Reid technique (FBI Method) – does not allow for sufficient protection of fundamental individual rights, even despite procedural guarantees. Effective protection is provided by non-coercive methods, which promote rapport and trust building – also strengthening the relationship between the state and the individual. The most significant impact in this sphere seems to be carried by the latest proposal – the Méndez Principles – which incorporates many individual methods, developed by researchers and practitioners alike, into a single comprehensive model, providing practical guidance addressed to law enforcement and practitioners and lawmakers. This consideration represents a novel approach to the issue, as the Méndez Principles have not yet been developed academically in the context of interrogation and human rights issues.